Generic bi-layered net model of a hybrid automation - Bánkuti, Gyöngyi; Csukás, Béla (Acta Agraria Kaposváriensis, 2003)
This paper describes an actual solution of the Single Switched Server problem, as well as suggests a methodology for a new representation of the hybrid automatons. The solution is based on the idea of Direct Computer Mapping and on the new conceptual modeling methodology called Generic, Bi-layered Net (GBN) approach. It is a novel framework for process simulation, as well as an adequate software technology that makes possible the common implementation of the hybrid (discrete & continuous) models. The very simple example for a Switched Server System illustrates how we can describe a „hybrid automaton” with this tool. Actually, the choice between the three possible products is controlled by the fuzzy evaluation functions, associated with the various storage volumes. The results show that the given system evolves into a periodic solution that is in good agreement with the other published approces.